Effect of Global ATGL Knockout on Murine Fasting Glucose Kinetics - Margarida Coelho; Patricia Nunes; Vera M. Mendes; Bruno Manadas; Arend Heerschap; John G. Jones (Journal of Diabetes Research)
Mice deficient in adipose triglyceride lipase (ATGL−/−) present elevated ectopic lipid levels but are paradoxically glucose-tolerant. Measurement of endogenous glucose production (EGP) and Cori cycle activity provide insights into the maintenance of glycemic control in these animals. These parameters were determined in 7 wild-type (ATGL+/−) and 6 ATGL−/− mice by a primed-infusion of [U-13C6]glucose followed by LC-MS/MS targeted mass-isotopomer analysis of blood glucose. EGP was quantified by isotope dilution of [U-13C6]glucose while Cori cycling was estimated by analysis of glucose triose 13C-isotopomers. Fasting plasma free fatty-acids were significantly lower in ATGL−/− versus control mice (0.43 ± 0.05 mM versus 0.73 ± 0.11 mM, P<0.05). Six-hour fasting EGP rates were identical for both ATGL−/− and control mice (79 ± 11 versus 71 ± 7 μmol/kg/min, resp.). Peripheral glucose metabolism was dominated by Cori cycling (80 ± 2% and 82 ± 7% of glucose disposal for ATGL−/− and control mice, resp.) indicating that peripheral glucose oxidation was not significantly upregulated in ATGL−/− mice under these conditions. The glucose 13C-isotopomer distributions in both ATGL−/− and control mice were consistent with extensive hepatic pyruvate recycling. This suggests that gluconeogenic outflow from the Krebs cycle was also well compensated in ATGL−/− mice.